Three Norwegian Varieties of a Nordic Model — A Historical Perspective on Working Life Relations - Heiret, Jan (Nordic Journal of Working Life Studies, 2012)
Through the use of a historical perspective, the aim of this article is to discuss and clarify the concurrent and conflicting interests and norms that have characterized the establishment and development of important institutions in Norwegian working life. The article concentrates on collective bargaining systems, the arrangements for codetermination, and the working environment regulations in both the public and private sector, which are regarded as the main institutions in the Norwegian and Nordic models of working life relations. The article is structured by an analytical distinction between three different historical periods that have constituted three distinct versions of the Norwegian model. By presenting a historical synthesis of Norwegian experiences, the article is a contribution to the ongoing debate on the varieties in the Nordic model, as to further comparisons and broader transnational studies.